Epistemology and Scientific Methodology in Āyurveda: The Means of Valid Knowledge According to the Rasavaiśeṣikasūtra and its Commentary by Narasiṃha - Vielle, Christophe (History of Science in South Asia, 2025)
This paper examines the means of valid knowledge (Sanskrit pramāṇas) according to Bhadanta Nāgārjuna’s Rasavaiśeṣikasūtra (4,70), an ancient Āyurvedic work (fourth-fifth centuries CE?), and its commentary by Narasiṃha (seventh-eighth centuries CE?). This theoretical treatise of medical philosophy on “the specifics of taste(s)” is, together with its bhāṣya, preserved in a single old palm-leaf manuscript from Kerala, an edition of which was published in print for the first time in Trivandrum in 1928. Both the sūtra-author and the commentator appear to have been Buddhist physicians. Following the sūtra, the pramāṇas are six, viz. perception (pratyakṣa), inference (anumāna), comparison (upamāna), tradition (āgama), implication (arthāpatti) and inclusion (saṃbhava). These are the same as in the Mīmāṃsā tradition except for the sixth. Quoted and parallel passages for this portion of Narasiṃha’s commentary are found in the works of the Buddhist logician Dignāga and in Candrakīrti’s Prasannapadā (commenting Nāgārjuna’s Mūlamadhyamakakārikās), as well as in the Carakasaṃhitā, the Nyāyabhāṣya, the Yuktidīpikā and other early commentaries to the Sāṃkhyakārikās 4-5, and in Vyāsa’s bhāṣya to the Yogasūtras (or Pātañjalayogaśāstra) 1,7. The examples provided for each pramāṇa are connected to medicine. Even if the same examples are commonly found in other epistemological, non-medical, sources, this feature is noteworthy and can be viewed as an indication of the milieu in which the pramāṇa theory originated or, at least, was used in a practical way. The interest of the commentary to RVS 4,70 and 3,44-45 also lies in its scientific approach to medical diagnostics and treatment, stressing observation and logical reasoning, and explaining, as in Carakasaṃhitā 3,4.5 (cf. 8.83), that traditional doctrine, which comes first as a means of knowledge, is itself ultimately based on perception and inference, what in modern times could be termed “empiricism”.